Foreign and domestic investment in global bond markets. - Park, Donghyun (Metro Manila, Philippines Asian Development Bank, 2018)
The Asian equity and bond markets have grown rapidly in the past decades. However, challenges have emerged including lack of liquidity, inactive institutional participation, and less favorable investor profiles. This paper analyzes the drivers of foreign versus domestic investment in global bond markets. The analysis suggests that there are some differences between foreign and domestic investors in both advanced and emerging bond markets. Foreign investors seem more sensitive to risk return profile than domestic investors, especially in emerging markets. They are also attracted by greater market openness and sound sovereign credit ratings. Finally, regional market integration can benefit emerging bond markets by broadening the investor base.
Keywords: Fiscal policy -- Developing countries; Industrial policy -- Developing countries; Electronic books